Utilization of N-Bromosuccinimide as a Brominating Agent for the Determination of Sumatriptan Succinate in Bulk Drug and Tablets - Kudige N. Prashanth; Kanakapura Basavaiah; Madihalli S. Raghu (International Journal of Analytical Chemistry)
One titrimetric and two spectrophotometric methods which are simple, sensitive, and economic are described for the determination of sumatriptan succinate (STS) in bulk drug and in tablet dosage form using N-bromosuccinimide (NBS) as a brominating agent. In titrimetry, aqueous solution of STS is treated with a measured excess of NBS in acetic acid medium, and after the bromination of STS is judged to be complete, the unreacted NBS is determined iodometrically (method A). Spectrophotometric methods entail addition of a known excess of NBS in acid medium followed by the determination of residual NBS by its reaction with excess iodide, and the liberated iodine () is either measured at 370 nm (method B) or liberated iodine is reacted with starch followed by the measurement of the blue colored starch-iodine complex at 570 nm (method C). Titrimetric method is applicable over range 1.0–10.0 mg STS (method A), and the reaction stoichiometry is found to be 1 : 3 (STS : NBS). The spectrophotometric methods obey Beer’s law for concentration range 0.6–15.0 μg mL−1 (method B) and 0.2–4.0 μg mL−1 (method C). The calculated apparent molar absorptivity values were found to be 2.10 × 104 and 7.44 × 104 L mol−1 cm−1, for method B and method C, respectively.